IDNLearn.com: Your go-to resource for finding expert answers. Our platform provides trustworthy answers to help you make informed decisions quickly and easily.
Sagot :
To find the difference of the given terms, we need to simplify each term individually first. Given:
[tex]\[ 2ab\left(\sqrt[3]{192 ab^2}\right) - 5\left(\sqrt[3]{81 a^4 b^5}\right) \][/tex]
[tex]\[ -3ab\left(\sqrt[3]{3ab^2}\right) \][/tex]
[tex]\[ 16ab^2\left(\sqrt[3]{3a}\right) - 45a^2b^2\left(\sqrt[3]{3b}\right) \][/tex]
[tex]\[ -7ab\left(\sqrt[3]{3ab^2}\right) \][/tex]
[tex]\[ 8ad\left(\sqrt[3]{3ab^2}\right) - 15ab^2\left(\sqrt[3]{3ab}\right) \][/tex]
Let's simplify each term one by one.
1. Simplifying [tex]\(2ab\left(\sqrt[3]{192ab^2}\right)\)[/tex]:
[tex]\[ \sqrt[3]{192ab^2} = \sqrt[3]{192} \cdot \sqrt[3]{a} \cdot \sqrt[3]{b^2} \][/tex]
[tex]\[ \sqrt[3]{192} = 192^{1/3} \][/tex]
So,
[tex]\[ 2ab \cdot 192^{1/3} a^{1/3} b^{2/3} \][/tex]
[tex]\[ = 2a^{1 + 1/3} b^{1+2/3} \cdot 192^{1/3} \][/tex]
[tex]\[ = 2a^{4/3} b^{5/3} \cdot 192^{1/3} \][/tex]
2. Simplifying [tex]\(-5\left(\sqrt[3]{81 a^4 b^5}\right)\)[/tex]:
[tex]\[ \sqrt[3]{81a^4b^5} = \sqrt[3]{81} \cdot \sqrt[3]{a^4} \cdot \sqrt[3]{b^5} \][/tex]
[tex]\[ = 81^{1/3} \cdots a^{4/3} \cdot b^{5/3} \][/tex]
[tex]\[ = 3a^{4/3} \cdot b^{5/3} = k_{1}a^{4/3}b^{5/3}\][/tex] , the [tex]\(81^{1/3}=3\)[/tex]
3. Simplifying [tex]\(-3ab\left(\sqrt[3]{3ab^2}\right)\)[/tex]:
[tex]\[ \sqrt[3]{3ab^2} = \sqrt[3]{3} \cdot \sqrt[3]{a} \cdot \sqrt[3]{b^2} \][/tex]
[tex]\[ = 3^{1/3} \cdots a^{1/3} \cdot b^{2/3} \][/tex]
[tex]\[ = ab \cdots 3^{1/3}a^{1/3}b^{2/3} = 3^{1/3}a^{4/3}b^{5/3}=k_{2}a^{4/3}b^{5/3}\][/tex], where we substituted to common [tex]\(k\)[/tex]
4. Simplifying [tex]\( 16ab^2\left(\sqrt[3]{3a}\right)-45a^2b^2\left(\sqrt[3]{3b}\right) \)[/tex]
[tex]\[ \sqrt[3]{3a} = 3^{1/3} a^{1/3} \][/tex]
[tex]\[ \sqrt[3]{3b} = 3^{1/3} b^{1/3} \][/tex]
The above are:
[tex]\[16ab^2\left(3^{1/3} a^{1/3}\right) - 45a^2b^2\left(3^{1/3} b^{1/3}\right) = k_{3}ab^{7/3}-k_4a^{7/3}b^2: k_{i} refers to constant term. 5. Simplifying \(-7ab\left(\sqrt[3]{3ab^2}\right)\): \[ \sqrt[3]{3ab^2} = \sqrt[3]{3} \cdot \sqrt[3]{a} \cdot \sqrt[3]{b^2} \][/tex]
[tex]\[ = 3^{1/3} \cdot a^{1/3} b^{2/3} \][/tex]
[tex]\[ = -7ab \cdot 3^{1/3} \cdot a^{1/3} b^{2/3} \][/tex]
[tex]\[ = -7ab \cdot 3^{1/3} \cdot a^{1/3} \cdot b^{2/3} \][/tex]
[tex]\[ = -7\cdot3^{1/3}a^{4/3} \cdot b^{5/3} \=k_nr term \rightarrow let all of this be k term\][/tex]
6. Simplifying[tex]\[8ad\left(\sqrt[3]{3ab^2}\right): \[8ad\left(3^{1/3}a^{1/3}b^{2/3}\right) - 15ab^2\left(\sqrt[3]{3ab}\right): Can be left unsolved \(\rightarrow combined together manually\][/tex]
Regards, определие наличия common terms \(2k_{1}-7_1) (k_{3}-k_4)
Use above result for final solution \[k_{1}+(-k)+("k_{{2}})=0
[tex]\[ 2ab\left(\sqrt[3]{192 ab^2}\right) - 5\left(\sqrt[3]{81 a^4 b^5}\right) \][/tex]
[tex]\[ -3ab\left(\sqrt[3]{3ab^2}\right) \][/tex]
[tex]\[ 16ab^2\left(\sqrt[3]{3a}\right) - 45a^2b^2\left(\sqrt[3]{3b}\right) \][/tex]
[tex]\[ -7ab\left(\sqrt[3]{3ab^2}\right) \][/tex]
[tex]\[ 8ad\left(\sqrt[3]{3ab^2}\right) - 15ab^2\left(\sqrt[3]{3ab}\right) \][/tex]
Let's simplify each term one by one.
1. Simplifying [tex]\(2ab\left(\sqrt[3]{192ab^2}\right)\)[/tex]:
[tex]\[ \sqrt[3]{192ab^2} = \sqrt[3]{192} \cdot \sqrt[3]{a} \cdot \sqrt[3]{b^2} \][/tex]
[tex]\[ \sqrt[3]{192} = 192^{1/3} \][/tex]
So,
[tex]\[ 2ab \cdot 192^{1/3} a^{1/3} b^{2/3} \][/tex]
[tex]\[ = 2a^{1 + 1/3} b^{1+2/3} \cdot 192^{1/3} \][/tex]
[tex]\[ = 2a^{4/3} b^{5/3} \cdot 192^{1/3} \][/tex]
2. Simplifying [tex]\(-5\left(\sqrt[3]{81 a^4 b^5}\right)\)[/tex]:
[tex]\[ \sqrt[3]{81a^4b^5} = \sqrt[3]{81} \cdot \sqrt[3]{a^4} \cdot \sqrt[3]{b^5} \][/tex]
[tex]\[ = 81^{1/3} \cdots a^{4/3} \cdot b^{5/3} \][/tex]
[tex]\[ = 3a^{4/3} \cdot b^{5/3} = k_{1}a^{4/3}b^{5/3}\][/tex] , the [tex]\(81^{1/3}=3\)[/tex]
3. Simplifying [tex]\(-3ab\left(\sqrt[3]{3ab^2}\right)\)[/tex]:
[tex]\[ \sqrt[3]{3ab^2} = \sqrt[3]{3} \cdot \sqrt[3]{a} \cdot \sqrt[3]{b^2} \][/tex]
[tex]\[ = 3^{1/3} \cdots a^{1/3} \cdot b^{2/3} \][/tex]
[tex]\[ = ab \cdots 3^{1/3}a^{1/3}b^{2/3} = 3^{1/3}a^{4/3}b^{5/3}=k_{2}a^{4/3}b^{5/3}\][/tex], where we substituted to common [tex]\(k\)[/tex]
4. Simplifying [tex]\( 16ab^2\left(\sqrt[3]{3a}\right)-45a^2b^2\left(\sqrt[3]{3b}\right) \)[/tex]
[tex]\[ \sqrt[3]{3a} = 3^{1/3} a^{1/3} \][/tex]
[tex]\[ \sqrt[3]{3b} = 3^{1/3} b^{1/3} \][/tex]
The above are:
[tex]\[16ab^2\left(3^{1/3} a^{1/3}\right) - 45a^2b^2\left(3^{1/3} b^{1/3}\right) = k_{3}ab^{7/3}-k_4a^{7/3}b^2: k_{i} refers to constant term. 5. Simplifying \(-7ab\left(\sqrt[3]{3ab^2}\right)\): \[ \sqrt[3]{3ab^2} = \sqrt[3]{3} \cdot \sqrt[3]{a} \cdot \sqrt[3]{b^2} \][/tex]
[tex]\[ = 3^{1/3} \cdot a^{1/3} b^{2/3} \][/tex]
[tex]\[ = -7ab \cdot 3^{1/3} \cdot a^{1/3} b^{2/3} \][/tex]
[tex]\[ = -7ab \cdot 3^{1/3} \cdot a^{1/3} \cdot b^{2/3} \][/tex]
[tex]\[ = -7\cdot3^{1/3}a^{4/3} \cdot b^{5/3} \=k_nr term \rightarrow let all of this be k term\][/tex]
6. Simplifying[tex]\[8ad\left(\sqrt[3]{3ab^2}\right): \[8ad\left(3^{1/3}a^{1/3}b^{2/3}\right) - 15ab^2\left(\sqrt[3]{3ab}\right): Can be left unsolved \(\rightarrow combined together manually\][/tex]
Regards, определие наличия common terms \(2k_{1}-7_1) (k_{3}-k_4)
Use above result for final solution \[k_{1}+(-k)+("k_{{2}})=0
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com is dedicated to providing accurate answers. Thank you for visiting, and see you next time for more solutions.